2006
DOI: 10.1080/08916150500317655
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Burner Geometry on Heat Transfer Characteristics of Methane/Air Flame Impinging on Flat Surface

Abstract: An experimental study has been conducted to find the heat transfer characteristics of methane/air flames impinging normally to a flat surface using different burner geometries. The burners used were of nozzle, tube, and orifice type each with a diameter of 10 mm. Due to different exit velocity profiles, the flame structures were different in each case. Because of nearly flat velocity profile, the flame spread was more in case of orifice and nozzle burners as compared to tube burner. Effects of varying the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Studies on numerical investigation are reported in the work of Conolly and Davies [7], Som et al [8], Chander and Ray [9] and Remie et al [6]. Different burner geometries (employing single and multiple jets) have been used, the inverse diffusion flame (IDF) burners have been employed by Dong et al [10][11][12][13][14] and burners with induced swirl by Huang et al [15], Chander and Ray [16,17] and Singh et al [18]. Following conclusions are drawn from the literature.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies on numerical investigation are reported in the work of Conolly and Davies [7], Som et al [8], Chander and Ray [9] and Remie et al [6]. Different burner geometries (employing single and multiple jets) have been used, the inverse diffusion flame (IDF) burners have been employed by Dong et al [10][11][12][13][14] and burners with induced swirl by Huang et al [15], Chander and Ray [16,17] and Singh et al [18]. Following conclusions are drawn from the literature.…”
Section: Introductionmentioning
confidence: 92%
“…The tube burner when compared with the orifice and nozzle has the maximum heat flux and surface temperature near the stagnation region, for the nozzle and orifice burners it is shifted away from the stagnation point [17]. The reason attributed to this is the velocity profile of the unburnt mixture exiting from these burners is different.…”
Section: Introductionmentioning
confidence: 96%
“…The non-equilibrium nature of the flow in this region also contributes to high heat flux values. Close to the high temperature reaction zone, large concentration of active species such as atoms and free radicals exist which augment convective heat transfer rates by diffusion and exothermic recombination in the boundary layer surrounding the heat receiving body [31,32]. Fig.…”
Section: Local Heat Flux Distribution For Different Configurationsmentioning
confidence: 99%
“…It has been seen that the heat flux distribution on the impingement surface is dependent upon the impinging flame shapes [15,16,[27][28][29][30][31]. All the flames were laminar (Re = 800) and appeared to be conical in shape with blue inner reaction zone and light blue outer layer.…”
Section: Impinging Flame Structurementioning
confidence: 99%
See 1 more Smart Citation